1994
DOI: 10.1295/polymj.26.953
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects on Thermotropic Liquid Crystal Polymer Alloys II. Effects of Third Component of Thermotropic Liquid Crystal Polymer on Mechanical Properties of Vectra A-Reinforced Poly(butylene terephthalate)

Abstract: ABSTRACT:The effects of addition of the 3rd component of thermotropic liquid crystal polymer (TLCP) on the mechanical properties and structure of Vectra A-reinforced poly(butylene terephthalate) (PBT) were studied. The 3rd TLCP was the copolymer based onp-hydroxybenzoate (PHB) and ethylene terephthalate, known as X-7G. PBT, Vectra A, and the third TLCP were blended in the molten state, the extrudate of which was cut and injection-molded. The mechanical properties of the blends were improved by the combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] TLCPs have been used for high performance engineering plastics due to their high strength and modulus, excellent thermal endurance and chemical stability. [10][11][12][13] They consist of rigid molecular chains, and exist as ordered domains in LC state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] TLCPs have been used for high performance engineering plastics due to their high strength and modulus, excellent thermal endurance and chemical stability. [10][11][12][13] They consist of rigid molecular chains, and exist as ordered domains in LC state.…”
Section: Introductionmentioning
confidence: 99%
“…The negative values of the χ 12 and B in PBT/TLCP composites suggested that TLCP was partially compatible with PBT in the melt state due to the physical entanglement and interaction between PBT and TLCP. 39 In addition, it can be deduced that the improvement of the compatibility for PBT/TLCP composites with lower TLCP content was attributed to the interaction between PBT chains and flexible PET units in TLCP phase. However, as TLCP content was increased above 10 wt%, the number of TLCP molecules in PBT/TLCP composites was increased, and the TLCP have a tendency to link themselves because of the interaction between TLCP molecules, resulting in the less interaction between TLCP and PBT molecules.…”
Section: Resultsmentioning
confidence: 99%
“…They are used in high‐performance engineering plastics because of their good mechanical properties and excellent thermal stability 1–4. The melt blending of TLCPs using conventional thermoplastics has attracted much attention due to the improved strength and tensile modulus of the resulting polymer composites 5–19. TLCPs show a high degree of order in the melt under shear and elongational flow fields, leading to deformation of the LC domains to form fibrils with high aspect ratios.…”
Section: Introductionmentioning
confidence: 99%